2021
DOI: 10.1111/josh.13055
|View full text |Cite
|
Sign up to set email alerts
|

Health Literacy and Food Literacy for K‐12 Schools in the COVID‐19 Pandemic

Abstract: BACKGROUND: Food literacy, a sub-area of health literacy, is achieving attention in schools, academia, research, health care, businesses, and governments worldwide. Against the current COVID-19 pandemic backdrop, the relevance of food literacy's interconnected attributes such as nutritional knowledge, food skills, and food environment is gaining traction. Enhancing health and food literacy in the K-12 school environment are important empowerment tools with the potential to reduce health inequalities as vulnera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Additional research would facilitate our ability to understand the entire landscape of literacy‐relevant models and frameworks. Another limitation was that the study scope did not examine the digital literacy needs of children and adolescents, which have been addressed elsewhere 81,82 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional research would facilitate our ability to understand the entire landscape of literacy‐relevant models and frameworks. Another limitation was that the study scope did not examine the digital literacy needs of children and adolescents, which have been addressed elsewhere 81,82 …”
Section: Discussionmentioning
confidence: 99%
“…Another limitation was that the study scope did not examine the digital literacy needs of children and adolescents, which have been addressed elsewhere. 81 , 82 …”
Section: Discussionmentioning
confidence: 99%
“…A rapid systematic review (n = 10 studies) revealed that healthy nutritional intake in many children and adolescents was adversely affected 20 . As a result, increased focus on health and food literacy in schools has been noted as a potential strategy to offset the nutrition impacts of COVID‐19 for young people 21 …”
Section: Social and Educational Impacts With Changes In Modes Of Lear...mentioning
confidence: 99%
“…A cognitive factor in the food choice framework that has received increasing attention over the last two decades and shares substantial conceptual connections with DB and health is the concept of food literacy (FL) [ 22 , 23 , 24 ]. FL describes how to find, understand, assess, and apply information with respect to one’s ability to plan, prepare, and consume food that is suitable or needed to promote health [ 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%